The genus Scirtes Illiger of Fiji (Coleoptera: Scirtoidea: Scirtidae) - Ruta, Rafał; Kiałka, Agata (Zootaxa, 2021)
Scirtes Illiger is the only genus of Scirtidae known to inhabit Fiji. In the present revision, 10 species of Scirtes are recorded from Fiji, including seven newly described. Scirtes humeralis Pic, S. natovensis Champion, and S. veitchi Champion are redescribed and illustrated. Scirtes evansi Pic is a junior synonym of S. natovensis. Both males and females of Fijian Scirtes have foveae on abdominal ventrite 2, a character unknown in other members of the genus. Lectotypes of Scirtes natovensis Champion, S. evansi Pic, and S. humeralis Pic are designated.